Gender culture and its provisions in Islamic legislation (Journal of the College of Basic Education, 2024)
Many Western ideas have spread in our Arab and Islamic world that have recently arrived and taken root in the Arab and Islamic mind and had a great impact on changing the ideas of the people of society. Among those ideas and cultures is the culture of gender or sexuality. This term, which has recently spread throughout the world, means separating the male and female genders and defining a new gender identity acquired from a person’s sense of himself and the characteristics he desires to have, such as a male living with a feminine identity, and the opposite for a woman, living with a masculine identity. Thus, we find that the new gender identity is not formed by the individual at the moment of birth, but is determined later by the individual’s social and psychological influences and factors.These Western ideas and cultures that are alien to Islamic societies have been adopted by the United Nations and international organizations, and approved by human rights organizations and Western laws, and they are considered an identity that any individual has the right to carry, without having anything to do with physical and organic differences between individuals and considering the imposition of equality that must be achieved between men and women. By adopting such ideas and cultures and encouraging the United Nations to enact such systematic laws, the intent of which is to spread corruption, obliterate religious identity, ignore the nature of God with which He created people, spread absolute freedom, and spread homosexuality without restrictions or limits, ignoring the Almighty’s saying: (O people, We have created you from a male and a female, and made you peoples and tribes so that you may know each other. Indeed, the most honorable of you in the sight of God is the most pious of you).It calls for the liberation of women from the restrictions of male control and domination and complete equality between them and men, reaching the concept of gender by exchanging roles between men and women without objection from members of society or the principles of divine religions, especially Islamic legislation. In this research, the researcher attempts to shed light on the concept of gender thought, its origins and culture, the most important reasons that led to the spread of this culture in our Islamic societies, and to clarify the Islamic ruling on it and ways to address it ideologically, intellectually and socially.